2020
DOI: 10.1055/a-1306-7590
|View full text |Cite
|
Sign up to set email alerts
|

Establishing key research questions for the implementation of artificial intelligence in colonoscopy: a modified Delphi method

Abstract: Background and Aims Artificial intelligence (AI) research in colonoscopy is progressing rapidly but widespread clinical implementation is not yet a reality. We aimed to identify the top implementation research priorities. Methods An established modified Delphi approach for research priority setting was used. Fifteen international experts, including endoscopists and translational computer scientists/engineers from 9 countries participated in an online survey over 9 months. Questions related to AI implementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 35 publications
0
39
0
Order By: Relevance
“…These potential advances are mainly expected from artificial neural networks, specifically deep learning-based methods 4 . Safe and efficient adoption of ML tools in clinical gastroenterology requires a thorough understanding of the performance metrics of the resulting models and confirmation of their clinical utility 5 .…”
mentioning
confidence: 99%
“…These potential advances are mainly expected from artificial neural networks, specifically deep learning-based methods 4 . Safe and efficient adoption of ML tools in clinical gastroenterology requires a thorough understanding of the performance metrics of the resulting models and confirmation of their clinical utility 5 .…”
mentioning
confidence: 99%
“…An example of a simple method that could be used to reduce FPs is re-training the CADe algorithms with scenarios that currently lead to FPs. Another approach could be the adoption of recurrent neural networks, which have memory and can process temporal sequences of frames in a way that is similar to the learning process of human brains [ 10 ]. Misawa et al reported that when they changed their old algorithm [ 17 ] to YoloV3 (You Only Look Once, Version 3), a state-of-the-art, real-time object detection algorithm, better specificity was achieved (increasing from 90.9% to 93.7%) [ 19 ].…”
Section: How To Address the Occurrence Of Fpsmentioning
confidence: 99%
“…An accompanying limitation of the CADe is false positives (FPs), which occur when the algorithm identifies a “polyp” that the endoscopist would disagree with. FPs were ranked 3rd in importance among 59 future research questions related to CADe [ 10 ]. Therefore, we conducted this systemic review on the definitions, causes, and adverse effects of the CADe FPs.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to compare different AI algorithms/settings/products due to the lack of established definition and measurement criteria for false-positive alarms in AI-assisted colonoscopy. This problem was also emphasized as one of the most crucial issues at a recent international expert meeting [4].…”
mentioning
confidence: 99%